Relations between Contact Duration, Type of Work Use of Personal Protective Equipment and Contact Dermatitis among Electroplaters - Danang Setia Budi (The Indonesian Journal of Occupational Safety and Health, 2020)
Introduction: Occupational contact dermatitis is defined as a skin disorder that occurs after work and caused by work process. Electroplating is one of the jobs which has  high contact dermatitis risk because there are irritant chemicals such as nickel and chromium. This study aimed to identify the relationship between risk factors for occupational-induced contact dermatitis and  electroplaters at CV. X and CV. Y, Durungbanjar Village, Sidoarjo District. Method: This research was an observational study using cross-sectional approach. The sample was a total population of 28 people, consisting of 13 electroplaters at CV. X and 15 electroplaters at CV. Y in Durungbanjar Village. The study was conducted in November - May 2019. Data were collected using questionnaires, observations and medical record sheets. The variables in this study were contact duration, contact frequency, type of work and the use of personal protective equipment. Result: Result showed that 64.3% of electroplaters suffered from contact dermatitis. Contact duration factor had a very strong correlation of c = 0.764, contact frequency factor had a strong correlation of c = 0.710, type of work had strong correlation of c = 0.616, personal hygiene factor had strong correlation of c = 0.547 and the use of personal protective equipment also had strong correlation of c = 0.545. Conclusion:  There is a very strong correlation between contact duration and contact dermatitis. Contact frequency, type of work and the use of personal protective equipment had strong correlation to contact dermatitis among electroplaters. The higher contact duration and frequency with irritant substances among the electroplaters, the higher the increase of the risk of contact dermatitis among the electroplaters. Some occupational efforts and recommendations can be made to reduce the risk of contact dermatitis. Keywords: contact dermatitis, electroplating, risk factors